2022
DOI: 10.1101/2022.07.10.499286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

baseLess: lightweight detection of sequences in raw MinION data

Abstract: With its candybar form factor and low initial investment cost, the MinION brought affordable portable nucleic acid analysis within reach. However, translating the electrical signal it outputs into a sequence of bases still requires high-end computer hardware, which remains a caveat when aiming for deployment of many devices at once or usage in remote areas. For applications focusing on detection of a target sequence, such as infectious disease or GMO monitoring, the computational cost of analysis may be reduce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The second group generates noisy sequence representations of the raw signal to compare them with the target reference [28,46]. The third group of works utilize neural network classifiers to label the sequences [29,47]. All these approaches are explained in detail in Section 7.…”
Section: Targeted Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…The second group generates noisy sequence representations of the raw signal to compare them with the target reference [28,46]. The third group of works utilize neural network classifiers to label the sequences [29,47]. All these approaches are explained in detail in Section 7.…”
Section: Targeted Sequencingmentioning
confidence: 99%
“…Therefore, unlike TargetCall, SquiggleNet cannot be used as a widely-applicable pre-basecalling filter. BaseLess [47] utilizes an array of small neural networks to detect a small subsequences from raw signals and match these subsequences with a target reference that share the same subsequence. This design choice provides a flexible solution that can define the set of pre-trained neural network models of subsequences to identify a certain target reference instead of retraining the neural network model for each species.…”
Section: Targeted Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the applicability of the mentioned method for complex inter-species classification is yet to be explored. The most recent work named baseLess is also a deep learning approach that relies on features of salient k-mers rather than reads as a whole, explicitly designed to work with MinION [17]. The authors have reported a performance similar to SquiggleNet, which does not surpass the performance of Guppy+Minimap2.…”
Section: Related Workmentioning
confidence: 99%
“…This renders many current methods [3, 6] inaccurate or useless for large genomes as they cannot either provide accurate results or match the throughput of nanopores for these genomes. Third, machine learning models used in past works [5, 8, 9] to analyze raw nanopore signals often require retraining or reconfiguring the model to improve accuracy for a certain experiment [11, 12], which can be a barrier to flexibly and easily performing realtime analysis without retraining or reconfiguring these models. To our knowledge, there is no work that can efficiently and accurately perform real-time analysis of raw nanopore signals on a large scale (e.g., whole-genome analysis for human) without requiring powerful computational resources, which can easily and flexibly be applied to a wide range of applications that could benefit from real-time nanopore raw signal analysis.…”
Section: Introductionmentioning
confidence: 99%